2020
DOI: 10.1002/adhm.201901819
|View full text |Cite
|
Sign up to set email alerts
|

Glutathione‐Depleting Nanoenzyme and Glucose Oxidase Combination for Hypoxia Modulation and Radiotherapy Enhancement

Abstract: Nanoenzymes perceive the properties of enzyme‐like catalytic activity, thereby offering significant cancer therapy potential. In this study, Fe3O4@MnO2, a magnetic field (MF) targeting nanoenzyme with a core‐shell structure, is synthesized and applied to radiation enhancement with using glucose oxidase (GOX) for combination therapy. The glucose is oxidized by the GOX to produce excess H2O2 in an acidic extracellular microenvironment, following which the MnO2 shell reacts with H2O2 to generate O2 and overcome h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
45
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 57 publications
0
45
0
Order By: Relevance
“…Tirapazamine, in contrast, is a prodrug that is activated under hypoxic conditions and can be administered as a complementary approach together with radiotherapy to treat hypoxic tumors 26 , 27 . Other researchers have explored direct intratumoral oxygen delivery strategies using hemoglobin 28 , perfluorocarbon-based nanoplatforms 24 , or enzyme-like nanoparticles capable of mediating in situ oxygenation by degrading endogenous H 2 O 2 and, thereby, overcoming hypoxia 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Tirapazamine, in contrast, is a prodrug that is activated under hypoxic conditions and can be administered as a complementary approach together with radiotherapy to treat hypoxic tumors 26 , 27 . Other researchers have explored direct intratumoral oxygen delivery strategies using hemoglobin 28 , perfluorocarbon-based nanoplatforms 24 , or enzyme-like nanoparticles capable of mediating in situ oxygenation by degrading endogenous H 2 O 2 and, thereby, overcoming hypoxia 29 , 30 .…”
Section: Introductionmentioning
confidence: 99%
“…But it is reported that ROS levels in some tumors are lower than corresponding non-tumorigenic cells (Diehn et al, 2009). Hence, two main strategies appears to be the key to solve these problems: (1) accurate tumor delineation and image guidance technologies with higher resolution (Bhide and Nutting, 2010); (2) highefficiency radiosensitizers to specifically increase the radiation deposition in tumors (Zhu et al, 2020a), reduce tumor hypoxia (Lyu et al, 2020b) and increase the production of reactive oxygen species in tumor cells (Liu et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, high-Z elements such as gold (Xia et al, 2020;Zhu et al, 2020a), silver (He et al, 2020;Khochaiche et al, 2021), platinum (Luo et al, 2020) and other nanoparticles (Deng et al, 2018) have been extensively explored as radiosensitizers. The tumor microenvironment (TME) is abundent in hydrogen peroxide (Balkwill et al, 2012;Taddei et al, 2013;Chen et al, 2017;Lyu et al, 2020b). Thus, nanoparticles containing manganese dioxide which could catalyze hydrogen peroxide to generate oxygen was used for alleviating hypoxia in tumors regions (Abbasi et al, 2016;Yi et al, 2016) and hence fix the DSBs in cells after radiotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Innovative MnO 2 nanoparticles (NPs) act as catalase in low-pH tumor microenvironments, leading to a reduced hypoxic state (Yang et al, 2017). A recent multi-use hollowed-out MnO 2 nanocatalyst successfully served its objectives to reduce hypoxic states and as a drug-delivery system (Lyu et al, 2020). Once introduced, this nanocatalyst accumulates within the kidneys and is eventually cleared out as Mn 2+ with minimal cytotoxicity effects (Zhao et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%